TESTING THE MEDIATION ROLE OF JOB SATISFACTION: THE INFLUENCE OF ORGANIZATIONAL CULTURE AND COMMUNICATION ON EMPLOYEE ENGAGEMENT IN MANUFACTURING COMPANIES - Sulistyowati, Pemilia; Manalu, Gibson; Wibowo, Eko Hari; Nur Cahyo, Taufik Galih; Zusrony, Edwin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study seeks to elucidate the influence of organizational culture and communication on employee engagement, mediated by job satisfaction among employees of a manufacturing company. This research employs a quantitative methodology. The population comprises all employees of manufacturing firms in Central Java. The sampling method employed is purposive sampling, including a total of 150 respondents. The data gathering instrument employs the Likert Scale. The data analysis employed SEM-PLS and was executed using SmartPLS software version 4.1.0.3. This research used the convergent validity test, composite reliability test, Cronbach's alpha test, average variance extracted test, r-squared test, and path coefficient analysis as its testing techniques. Data analysis results utilizing statistical tests demonstrate that corporate culture and communication significantly influence employee engagement, with job satisfaction serving as a mediating factor.